Strategi Peningkatan Kualitas Sumber Daya Manusia Sebagai Pasukan Perdamaian di Pusat Misi Pemeliharaan Perdamaian TNI (PMPP TNI) - Handoyo, Hengki; Muslim, Muh. Azis (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to identify strategies for improving the quality of human resources as peacekeepers at the TNI Peacekeeping Mission Center (PMPP TNI). Using qualitative methods, this research explores strategies that can be implemented to enhance the quality of human resources at PMPP TNI. Through an analysis of relevant texts and literature, this study emphasizes the importance of developing quality leadership and planned human resource development in the context of global peacekeeping missions. The findings of this study reveal the complexity of the challenges faced in implementing these strategies, including the need for international collaboration in knowledge and technology exchange. The implications of these findings indicate that a holistic and targeted approach is necessary to achieve the goal of improving human resource quality in peacekeeping training. Additionally, this research underscores the importance of cross-border collaboration in training technology to achieve optimal training independence. This study provides valuable contributions for policymakers and practitioners in formulating strategies to enhance the quality of human resources as part of efforts to maintain world peace